2002
DOI: 10.1091/mbc.01-09-0446
|View full text |Cite
|
Sign up to set email alerts
|

Utrophin Binds Laterally along Actin Filaments and Can Couple Costameric Actin with Sarcolemma When Overexpressed in Dystrophin-deficient Muscle

Abstract: Dystrophin is widely thought to mechanically link the cortical cytoskeleton with the muscle sarcolemma. Although the dystrophin homolog utrophin can functionally compensate for dystrophin in mice, recent studies question whether utrophin can bind laterally along actin filaments and anchor filaments to the sarcolemma. Herein, we have expressed full-length recombinant utrophin and show that the purified protein is fully soluble with a native molecular weight and molecular dimensions indicative of monomers. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 56 publications
5
101
0
Order By: Relevance
“…Dystrophin-related protein or utrophin is considered the autosomal homologue of dystrophin, because it shares extensive sequence homology as well as its size and abundance in muscle (Love et al, 1989;Khurana et al, 1990;Tinsley et al, 1992). Utrophin and dystrophin also share functional properties such as the ability to associate with the dystroglycan complex and bind F-actin (Matsumura et al, 1992;Winder and Kendrick, 1995;Rybakova et al, 2002). Direct evidence for the ability of utrophin to functionally substitute comes from experiments demonstrating that utrophin overexpression driven either by transgenic means Rafael et al, 1998;Tinsley et al, 1998;Fisher et al, 2001) or viral vectors (Gilbert et al, 1999;Wakefield et al, 2000;Cerletti et al, 2003) can rescue dystrophin-deficient muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Dystrophin-related protein or utrophin is considered the autosomal homologue of dystrophin, because it shares extensive sequence homology as well as its size and abundance in muscle (Love et al, 1989;Khurana et al, 1990;Tinsley et al, 1992). Utrophin and dystrophin also share functional properties such as the ability to associate with the dystroglycan complex and bind F-actin (Matsumura et al, 1992;Winder and Kendrick, 1995;Rybakova et al, 2002). Direct evidence for the ability of utrophin to functionally substitute comes from experiments demonstrating that utrophin overexpression driven either by transgenic means Rafael et al, 1998;Tinsley et al, 1998;Fisher et al, 2001) or viral vectors (Gilbert et al, 1999;Wakefield et al, 2000;Cerletti et al, 2003) can rescue dystrophin-deficient muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Dystrophin and its associated proteins are enriched at all these sites (Porter et al, 1992;Williams and Bloch, 1999a;Williams et al, 2000). When it is present, the dystrophin complex helps to link the contractile apparatus to the sarcolemma and through the membrane to the extracellular matrix (Ibraghimov-Beskrovnaya et al, 1992;Ervasti and Campbell, 1993;Rybakova et al, 2000;Rybakova et al, 2002; Michele et al, 2003). When dystrophin is absent, links between the contractile apparatus and the sarcolemma can weaken and eventually break (Porter et al, 1992;Ehmer et al, 1997;Williams and Bloch, 1999b;Rybakova et al, 2000), damaging the sarcolemma (Mokri and Engel, 1975), and, ultimately, killing the myofiber (reviewed in Emery, 1993).…”
mentioning
confidence: 99%
“…Transgenic expression of the dystrophin homolog utrophin restored the stable association of costameric actin with the sarcolemma [5]. Most recently, we demonstrated that γ cyto -actin protein levels were elevated 10-fold in striated muscle from the dystrophin-deficient mdx mouse [6].…”
Section: Introductionmentioning
confidence: 73%
“…The actin binding proteins γ-filamin, talin, vinculin, plectin and utrophin are all upregulated and/or redistributed to costameres in dystrophin-deficient muscle [4,5,[32][33][34]. With the exception of utrophin, all of these proteins interact with integrins in vivo and α7β1 integrin is also upregulated in dystrophin-deficient muscle [35,36].…”
Section: Resultsmentioning
confidence: 99%